Potential of CO2-EOR for Near-Term Decarbonization - Núñez-López, Vanessa; Moskal, Emily (Frontiers in Climate, 2019)
This paper provides an overview of carbon dioxide enhanced oil recovery (CO2-EOR) and its ability to reduce greenhouse gas (GHG) emissions (even to the point of negative emissions), the role it needs to play in the challenge of decarbonization, and the need to scale up implementation and deployment in order to meet climate goals. Limitations in current legal and regulatory frameworks for CO2 injection are explored for both economic and environmental purposes, as well as the economic implications of combining CO2-EOR with geologic carbon storage. Results from a recent study, which demonstrate that all CO2-EOR operations produce negative emissions oil during the first several years of production, are analyzed in the context of the urgency of climate change mitigation. Acknowledging that fossil fuels currently provide the energy foundation upon which global societies function, and that a sudden shift in the composition of that foundation can potentially destabilize the global economy and key elements of modern society, we bring CO2-EOR to the fore as it can supply reduced carbon oil to support the current energy foundation as it steadily transitions toward decarbonization. In order to meet this urgent transition, greater fiscal and regulatory incentives are needed to begin scaling CO2-EOR with storage around the globe. A viable and large-scale CO2-EOR/storage industry depends upon significant capital investments for CO2 capture and transportation infrastructure. Policy consistency and predictability, combined with targeted subsidies, will help to achieve this goal.